Unpacking the perceptions and experiences of student facilitators in interprofessional education: a qualitative study - Qing He; Junru Lei; Doris Chong; Pauline Luk; Enoch Chan; Xiaoai Shen; George Lim Tipoe; Linda Chan; Michael M. Manio; John Ian Wilzon T. Dizon; Fraide A. Ganotice (Medical Education Online)
Enhancing health professional students’ effective learning and collaborative practice requires a deep understanding of strategies for facilitating interprofessional learning. While faculty members and clinical preceptors are recognized as facilitators in interprofessional education (IPE), there is limited knowledge about the impact of student facilitators’ engagement in IPE. Accordingly, this study aims to explore the perceptions and experiences of student facilitators in IPE. Thirteen student facilitators were recruited to lead an interprofessional learning program, and they were subsequently invited to participate in one-on-one interviews. An interview guide was developed to explore their motivations, expectations, engagement, effectiveness, and achievements in IPE facilitation. Thematic analysis was conducted using MAXQDA software to analyze the student facilitators’ experiences and perceptions. Eight interviewees from various disciplines, including Medicine, Nursing, Pharmacy, Speech and Hearing Sciences, and Social Work, took part in the study. The findings revealed that student facilitators highly valued their IPE facilitation experience, which aligned with their expectations and led to the creation of social networks, increased confidence, improved understanding of other professions, and the development of lifelong skills. Furthermore, the student facilitators demonstrated cognitive and social congruence by establishing a relaxed learning environment, displaying empathetic and supportive behaviors, and using inclusive language to engage IPE learners in group discussions. This study provides a comprehensive understanding of the role of student facilitators in IPE, contributing to the evolving literature on IPE. A conceptual framework was developed to explore the entire facilitation experience, encompassing the motivations and expectations of student facilitators, their engagement and effectiveness, and the observed achievements. These findings can inform the development of peer teaching training in IPE and stimulate further research in identifying relevant facilitator competencies for optimal delivery of IPE.